Being Henry : the Fonz . . . and beyond - Winkler, Henry, 1945-; Kaplan, James, 1951- (Celadon Books, 2023)
"From Emmy-award winning actor, author, comedian, producer, and director Henry Winkler, a deeply thoughtful memoir of the lifelong effects of stardom and the struggle to become whole. Henry Winkler, launched into prominence as "The Fonz" in the beloved Happy Days, has transcended the role that made him who he is. Brilliant, funny, and widely-regarded as the nicest man in Hollywood (though he would be the first to tell you that it's simply not the case, he's really just grateful to be here), Henry shares in this achingly vulnerable memoir the disheartening truth of his childhood, the difficulties of a life with severe dyslexia, the pressures of a role that takes on a life of its own, and the path forward once your wildest dream seems behind you. Since the glorious era of Happy Days fame, Henry has endeared himself to a new generation with roles in such adored shows as Arrested Development, Parks and Recreation, and Barry, where he's been revealed as an actor with immense depth and pathos, a departure from the period of his life when he was so distinctly typecast as The Fonz, he could hardly find work. Filled with profound heart, charm, and self-deprecating humor, Being Henry is a memoir about so much more than a life in Hollywood and the curse of stardom. It is a meaningful testament to the power of sharing truth and kindness and of finding fulfillment within yourself"--